Traditional Chinese medicine (Lianhua Qingwen) as an add-on to Western medicine for mild to moderate COVID-19 patients: A meta-analysis - Daniel Kwok-keung Ng; Shuk-yu Leung; Yi-tak Au; Han-dong Li; Wei-bin Feng; Chi-hang Yum; Kam Lun E Hon (Pediatric Respirology and Critical Care Medicine)
Background: Proprietary traditional Chinese medicine (TCM) such as Lianhua Qingwen (LQ) has been promoted to be an over-the-counter product for treating infectious diseases including COVID-19. This meta-analysis aimed to evaluate the efficacy of LQ in adults with mild or moderate COVID-19 diseases. Materials and Methods: The authors conducted the literature search using six electronic databases (Chinese and English) from the inception dates of the different database to October 31, 2022, using search for relevant keywords, that is, “severe acute respiratory syndrome coronavirus 2,” “COVID-19,” “Lianhuaqingwen,” and “Lianhua Qingwen” to identify randomized controlled trials (RCTs). Three reviewers independently identified studies, extracted the data, and assessed study quality. All analyses were conducted on RevMan 5.3. Results: A total of 6 RCT studies involving patients with COVID-19 were identified according to the inclusion and exclusion criteria. The quality of included studies was moderate. LQ was effective in improving overall clinical efficacy (RR = 1.25; 95% CI: 1.14–1.36; P < 0.001), and relieved three features, that is, cough (WMD = –2.04; 95% CI: –3.92 to –0.17; P = 0.03), fatigue (WMD= –2.58; 95% CI: –3.45 to –1.71; P < 0.001), and chest CT resolution (RR = 1.21; 95% CI: 1.02–1.43; P = 0.03) but not resolution of fever (WMD = –0.46; 95% CI: –1.54 to 0.62; P = 0.40) among adults with mild or moderate COVID-19. LQ was also effective in reducing the rate of conversion to severe cases (RR = 0.57; 95% CI: 0.37–0.86; P = 0.007). The adverse events rate (RR = 0.74; 95% CI: 0.40–1.37; P = 0.35) were similar between LQ group and the control group. Conclusion: This meta-analysis of six RCT shows that the Lianhua Qingwe (LQ) as an add-on to Western medicine achieves a higher overall clinical efficacy, faster resolution of cough, fatigue and chest CT changes than Western medicine alone in COVID patients. LQ is also effective in reducing the rate of conversion to severe cases. Further double-blinded placebo-controlled randomized studies are warranted for LQ as a stand-alone treatment for the “heat” subtype of mild to moderate COVID diseases.